Lexin: Swedish-Persian dictionary - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish-Persian (Fārsī) dictionary for immigrants who want to learn Swedish. Includes commonly used words and phrases as well as words from Swedish society.

text/xml

Svensk-persiskt lexikon lexikon för invandrare som vill lära sig svenska. Lexikonet omfattar vanligt förekommande ord och fraser samt samhällsord som är viktiga för den som vill orientera sig i det svenska samhället.

text/xml
Lexin: Svensk-persiskt lexikon
Keywords: everyday life; vardagsliv; lexicon; lexikon; society; samhälle; lexin; lexin; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur